2007
DOI: 10.1523/jneurosci.1992-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Hearing Loss Disrupts Synaptic and Spike Adaptation in Developing Auditory Cortex

Abstract: Although sensorineural hearing loss (SNHL) is known to compromise central auditory structure and function, the impact of milder forms of hearing loss on cellular neurophysiology remains mostly undefined. We induced conductive hearing loss (CHL) in developing gerbils, reared the animals for 8 -13 d, and subsequently assessed the temporal features of auditory cortex layer 2/3 pyramidal neurons in a thalamocortical brain slice preparation with whole-cell recordings. Repetitive stimulation of the ventral medial ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
105
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 90 publications
7
105
1
Order By: Relevance
“…are determined by the sensory deprivation paradigm as well as cortical layers. Similar homeostatic intrinsic plasticity results have been reported in the auditory system, where hearing loss raised intrinsic biophysical excitabilities (Kotak et al 2005;Xu et al 2007). …”
Section: Intrinsic Plasticity Induced By Activity-dependent Versus Hosupporting
confidence: 77%
See 3 more Smart Citations
“…are determined by the sensory deprivation paradigm as well as cortical layers. Similar homeostatic intrinsic plasticity results have been reported in the auditory system, where hearing loss raised intrinsic biophysical excitabilities (Kotak et al 2005;Xu et al 2007). …”
Section: Intrinsic Plasticity Induced By Activity-dependent Versus Hosupporting
confidence: 77%
“…To date, intrinsic plasticities have been described primarily in principal neurons in the visual (Cudmore and Turrigiano 2004;Maffei and Turrigiano 2008;Maffei et al 2004), auditory (Xu et al 2007), and somatosensory cortices (Barth et al 2004). In these studies, the intrinsic plasticities exhibited either enhanced or reduced excitabilities and are induced via different physiological mechanisms (e.g., sensory deprivation or acute long-term pairing), respectively.…”
Section: Ionic Mechanisms Underlying the Effects Of Whisker Experiencmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrophysiological investigations of conductive hearing loss (CHL) in animals have shown that CHL changes the way sound is processed in the peripheral and central auditory system (e.g., Clopton and Silverman, 1978;Webster and Bobbin, 1986;Sumner et al, 2005;Xu and Jen, 2001;Jen and Xu, 2002;Xu et al, 2007). Centrally, unilateral CHL results in a decrease in glucose uptake as measured by the 2-deoxyglucose (2-DG) method, affecting cellular activity and metabolism in the major afferent projection from the manipulated ear (e.g., Tucci et al, 1999Tucci et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%